Investigation of the incidence of use of quinine sulphate as a contraceptive in the Hillbrow- Berea area - Jugram, Nishaan (My University, 2003)
Quinine is a naturally occurring alkaloid found in the bark of the South American cinchona tree. It is used to treat malaria, to relieve nocturnal leg cramps and is used as an antipyretic. Anecdotal evidence, especially from community pharmacists, suggests widespread misuse of quinine sulphate. It has been taken for a range of non-indicated uses ranging from a single dose monthly contraceptive to a post coital “morning after” contraceptive. A self-administered questionnaire, together with a confidentiality and anonymity declaration, was offered to all females requesting quinine sulphate at a pharmacy in Hillbrow, Johannesburg. After completing the questionnaire, the participants were counselled on the proper indications, as well as the consequences of misuse of quinine.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Medicine in Pharmaceutical Affairs. Johannesburg, 2003
Keywords: Contraceptive Agents, Female [Pharmacological Action]; Quinine; Sulfates